On privacy - Véliz, C (2017)
This thesis concerns the ethics and political philosophy surrounding privacy. It investigates what privacy is, what is at stake in its loss, and how it relates to other rights and values. The first part sets the groundwork for the rest of the thesis. Chapter One delves into the origins of privacy. I argue that privacy is not a recent cultural product, but rather a need buried deep in our evolutionary and human history. The second part of the thesis is dedicated to conceptual issues. Chapter Two clarifies the relation between privacy and the public and private divide. I argue against the popular belief that privacy is an issue that belongs solely to the private sphere. Chapter Three reviews the most influential definitions of privacy that have been offered in the legal and philosophical literature, and points out some of their shortcomings and strengths. In Chapter Four, I develop my own definition of privacy as remaining personally unaccessed, as well as an account of the right to privacy as a right to a robustly demanding good. I also map out the moral significance of privacy perceptions, and privacy-related obligations. The third part of the dissertation concerns practical issues. Chapter Five inquires into the relationship between security and privacy. I argue that mass surveillance is a disproportionate, unnecessary, and ineffective response to the threat of terrorism. I also argue that encryption should be widely used, as it can curtail the mass surveillance of content and protect people without seriously obstructing criminal investigations. Chapter Six explores the relationship between privacy and transparency. I argue that transparency should sometimes be limited in the interest of privacy. Chapter Seven deals with the questions of whether we can lose privacy to computer algorithms, and whether decision-making algorithms can violate our right to privacy. I answer both questions in the negative, as algorithms are currently neither our peers nor moral agents responsible for their actions. The conclusion sketches some of the lessons learnt over the course of this investigation.